(untitled) (Web of Teachers: Inderscience Research, 2025)
This article is written about the methods of scientific and creative work of physical culture students. In this, the purpose and direct tasks of the scientific-theoretical research occur in a number of individual phenomena, opinions and considerations are given about the laws of the emergence, operation, and development of such phenomena.